Soil microbial community composition and diversity in the rhizosphere of Alsophila spinulosa growing in different habitats within the Chishui Alsophila National Nature Reserve in Guizhou Province, China - Che, Bingjie; Yang, Weicheng; He, Qinqin; Jiang, Yu; Zhang, Bingchen; Chen, Hangdan (Frontiers in Microbiology, 2024)
The rhizosphere is considered a highly complex and dynamic ecosystem. Rhizosphere soil microorganisms influence the growth and development of plants by mediating the transformation and absorption of nutrients. In order to explore the microbial community composition and diversity of Alsophila spinulosa growing in different habitats. Rhizosphere samples were collected from four different habitats within the Chishui Alsophila National Nature Reserve in Guizhou Province, China. According to the high-throughput sequencing results of 16 s rDNA and ITS, Proteobacteria and Ascomycota were the most abundant bacterial and fungal phyla in the rhizosphere soil of all four habitats. The alpha diversity analysis indicated that two particular habitats, Buddha Rock and Botanical Garden, harbored the highest microbial richness and diversity. LEfSe analysis revealed that Buddha Rock contained the highest relative abundance of Bacteroidetes compared to the other three study areas. Meanwhile, Tiantang Gou contained the highest relative abundance of Basidiomycota. Bacterial community composition and diversity were greatly influenced by soil pH, while fungal community composition and diversity were greatly influenced by available phosphorus, organic carbon, sucrase, and urease. The results of this study provide a scientific basis for the habitat restoration of A. spinulosa, and the improvement of the structure of the A. spinulosa rhizosphere soil microbial community. Laying a theoretical foundation for the next screening of inter-root functional flora.